Global Trends in Quality Education Research under ESD and the 2030 Agenda: A Bibliometric Review - Mochammad Ja'far Amri Amanulloh; Raden Bambang Sumarsono; A Supriyanto (Tarbawi: Jurnal Keilmuan Manajemen Pendidikan, 2025)
This study explores research trends on quality education within the Education for Sustainable Development (ESD) framework and the 2030 Agenda. This study uses a bibliometric analysis approach to identify key publication developments from 2020 to 2024. The data was retrieved from Scopus-indexed journals and analyzed using R and VOSviewer software. The study's analysis encompassed 442 relevant articles, meticulously interpreted according to the established criteria. The findings of this study indicate an increase in the number of publications each year (except 2021), with almost all types of scientific papers being articles (70%) in Social Science studies as the largest field of study. The study also interprets the number of publications and the impact of scientific papers through citations containing the source of articles, authors, institutions, and countries with fluctuations in each criterion. The frequently utilized keywords can be categorized into eight color clusters, demonstrating the keyword usage level. The study's limitations are evident in its periodization, approach, and data distribution. Notwithstanding these limitations, the study offers pertinent implications for establishing new trends in future research. In particular, in the fields of research, public policy, and education, the findings of this study have significance for improving the quality of education at every level, from schools to universities.